A representaç\~ao social do estudo e do trabalho na vida cotidiana de jovens de classes populares - Enid Rocha Andrade Silva; Valéria Rezende (Instituto de Pesquisa Econômica Aplicada (IPEA), 2021)
– In this article, we analyze the role of work and study activities in the daily lives of young people aged 18 to 24, who live in low-income families in the city of Recife, Pernambuco. The dream of continuing to study or resuming the trajectory of studies is present as a central element in the lives of all young people surveyed, representing the great hope of social mobility, even for young people who were not studying and not employed.
Keywords: J15; J16; J18; 330; youth; education; labor market; early pregnancy; inequality; poverty